Recent Progresses in the Design and Fabrication of Highly Efficient Ni-Based Catalysts With Advanced Catalytic Activity and Enhanced Anti-coke Performance Toward CO2 Reforming of Methane - Wu, Xianyun; Xu, Leilei; Chen, Mindong; Lv, Chufei; Wen, Xueying; Cui, Yan; Wu, Cai-e; Yang, Bo; Miao, Zhichao; Hu, Xun (Frontiers in Chemistry, 2020)
CO2 reforming of methane (CRM) can effectively convert two greenhouse gases (CO2 and CH4) into syngas (CO + H2). This process can achieve the efficient resource utilization of CO2 and CH4 and reduce greenhouse gases. Therefore, CRM has been considered as a significantly promising route to solve environmental problems caused by greenhouse effect. Ni-based catalysts have been widely investigated in CRM reactions due to their various advantages, such as high catalytic activity, low price, and abundant reserves. However, Ni-based catalysts usually suffer from rapid deactivation because of thermal sintering of metallic Ni active sites and surface coke deposition, which restricted the industrialization of Ni-based catalysts toward the CRM process. In order to address these challenges, scientists all around the world have devoted great efforts to investigating various influencing factors, such as the option of appropriate supports and promoters and the construction of strong metal-support interaction. Therefore, we carefully summarized recent development in the design and preparation of Ni-based catalysts with advanced catalytic activity and enhanced anti-coke performance toward CRM reactions in this review. Specifically, recent progresses of Ni-based catalysts with different supports, additives, preparation methods, and so on, have been summarized in detail. Furthermore, recent development of reaction mechanism studies over Ni-based catalysts was also covered by this review. Finally, it is prospected that the Ni-based catalyst supported by an ordered mesoporous framework and the combined reforming of methane will become the future development trend.